PELATIHAN PENAMAAN USAHA KULINER BERBASIS BUDAYA SUNDA BAGI IBU-IBU UMKM DI DESA CIKAJANG, GARUT - citraresmana, Elvi; Rachmat, Ani; Sidiq, Inu Isnaeni (Midang, 2025)
Business naming constitutes a vital component in the entrepreneurial landscape, particularly within the highly competitive culinary sector. An appropriate and culturally resonant business name not only conveys the identity of a product but also communicates embedded values, meanings, and cultural familiarity to target consumers. In Cikajang Village, Garut Regency, the majority of culinary micro-entrepreneurs are housewives operating small-scale enterprises with limited access to marketing knowledge and branding strategies. Despite facing economic challenges and possessing low purchasing power, these women exhibit strong motivation and commitment to advancing their businesses. This community engagement initiative was designed to provide capacity-building through a culturally grounded training program on culinary business naming, drawing from Sundanese cultural values. The training was conducted over a one-month period using a participatory approach involving lectures, group discussions, and practical workshops. Participants were guided to formulate business names that reflect key Sundanese cultural principles such as kinship, hospitality, and authenticity of taste. In addition, they were introduced to basic promotional strategies including word-of-mouth marketing, elementary social media engagement, and the design of product labels. The results indicate that most participants were able to produce distinctive and culturally anchored business names, and began applying the promotional tools introduced during the training. This initiative not only enhanced awareness of branding’s significance in micro-enterprises but also demonstrated the effectiveness of a culturally sensitive approach to empowering women entrepreneurs. It is anticipated that this model may be replicated and adapted for the sustainable development of traditional MSMEs in other culturally rich rural settings.